Levels of plasma malondialdehyde and erythrocyte antioxidant enzyme activities in patients with chronic hepatitis B - Demirdag, K; Yilmaz, S; Ozdarendeli, A; Ozden, M; Kalkan, A; Kilic, SS (H G E Update Medical Publishing S A, 2003)
Background/Aims: Hepatitis B virus infection, extensively seen throughout the world, can become highly chronic. Pathogenesis of chronic hepatitis is not yet known fully. It is shown that oxidative stress may play a role in pathogenesis and may regulate collagen synthesis and thus may contribute to the process of liver damage. This study is aimed at investigating the existence of oxidative stress in chronic hepatitis B cases and its relation with alanine aminotransferase and aspartate aminotransferase which are the serum indicators of liver damage; along with interaction of erythrocyte antioxidation enzyme activities in the same cases. Methodology: Eighty patients with chronic hepatitis B under follow-up, and 40 healthy volunteers were included in this study. In the control and patient groups, together with serological markers for viral etiology, alanine aminotransferase and aspartate aminotransferase levels; plasma malondialdehyde level; erythrocyte superoxide dismutase, glutathione peroxidase and catalase activities were analyzed. Results: Malondialdehyde levels of chronic hepatitis B cases were statistically high compared to control group (p<0.05). There was correlation between serum malondialdehyde levels and serum alanine aminotransferase, aspartate aminotransferase levels in the patient group (r = 0.324, p<0.01, r = 0.273, p<0.05). Average superoxide dismutase and catalase activities were found to be significantly low compared to control group (p<0.001); average glutathione peroxidase activity were significantly high when considered statistically (p<0.001). No correlation between serum alanine aminotransferase and aspartate aminotransferase levels and glutathione peroxidase, catalase and superoxide dismutase activities was found in the patient group (p>0.05). Conclusions: In the study we showed that there is' correlation between serum malondialdehyde level and alanine aminotransferase and aspartate aminotransferase levels of chronic hepatitis B patients. According to the results of our study, it might be thought that serum malondialdehyde level might be a marker of hepatocellular damage in chronic hepatitis B cases. We suggest that antioxidant treatment for chronic hepatitis B patients should be examined in future studies.
Keywords: hepatitis B; malondialdehyde; superoxide dismutase; glutathione peroxidase; catalase